EU-Indonesia Trade - Szamałek, Michał (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
My work shows the problem of trade between the EU and Indonesia, the problem is quite significant because Indonesia is a developing country and has a lot of economic potential. The research objective of my work was to bring the reader closer to the EU-Indonesia trade relations and to describe the structure of these relationships. The research methodologies that I used to do my work are first of all the analysis of data provided by the European Union and the analysis of documents and articles. The implications of this work are that I have a lot of potential in Indonesia and that as an economic leader in the Southeast Asia region it is likely to become a very great and valuable ally of the EU. I hope the reader after reading the work will get answers to all the major questions about the topic.